Dynastic politics, international Protestantism and royal rebellion: Prince George of Denmark and the Glorious Revolution - Farguson, J (Oxford University Press, 2016)
This article reveals the importance of Prince George of Denmark to James II and William of Orange. It places George in the world of early modern European politics, when foreign policy and international relations were inextricably linked with dynastic politics, and many were concerned about the future well-being of Protestantism. The religious component is crucial as the evidence strongly suggests that George felt he belonged to a ‘Protestant International’, not defined by membership of a particular nation. By drawing attention to the polycentric nature of the Stuart court in the 1680s, the workings of dynastic politics in the international arena that involved secret political manoeuvrings in the run up to the invasion, and then detailing the way in which George behaved following William’s arrival, this article argues that Prince George played a crucial role in the Glorious Revolution. It will also demonstrate that in the 1690s George helped to consolidate and promote the new regime. During the period in question the Prince and Princess of Denmark were a political partnership, and rather than being led by others, they joined forces with William and Mary because they each had a distinct political agenda. George pursued policies he believed would benefit the Stuart–Oldenburg dynasty in England, and its related houses in Europe, and the cause of international Protestantism. A subsidiary theme of this article will be the continuing importance of ceremonies involving royalty to the political culture of urban communities in early modern England.